Optimalisasi Performa Sistem Tegangan dengan Pemasangan Kapasitor Bank pada Pembangkit Listrik Tenaga Uap (PLTU) Nagan Raya - Syukri, Mahdi; Suriadi; Sara, Ira Devi; Siregar, Ramdhan Halid; Muhibbuddin; Masri (Yayasan Kawanad, 2023)
This research aims to optimize the performance of the voltage system at the Nagan Raya Steam Power Plant (PLTU) by installing capacitor banks. Capacitor banks are integrated into the system to increase voltage stability, reduce power losses, and increase energy efficiency in PLTUs. The research method involves analyzing the existing voltage system, designing the capacitor bank installation, and evaluating the system performance after installation. It is hoped that the results of this research can make a positive contribution in improving the performance of PLTU Nagan Raya and overall energy efficiency.